Relationship Between Early Complex Food Practice with Nutritional Status Among Children Age 7 to 23 Months - Megasari, Megasari; Mariyani, Mariyani (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims:: Knowing the factors associated with the practice of early complementary feeding with the nutritional status of infants aged 7 to 23 months in Sipayung Village, Cipanas District, Lebak Regency. Method: A cross-sectional design was used for quantitative and analytical study. A purposive sampling method was used to choose 51 mothers with babies between the ages of 7 and 23 months as the study sample. A questionnaire was used as the study tool. The square test was used to look at the primary data. Result: The single-variable study showed that 82.4% of infants had good nutrition and 72.5% of those who were given MP ASI did so correctly. The bivariate analysis showed that there was a link between the number of times MP-ASI was given, the age at which it was first given, how often it was given, how consistently it was given, and the infant's nutritional status (p value = 0.000). Conclusion: The practice of giving MP-ASI has to do with how well babies ages 7 to 23 months are eating. Mothers of babies should always pay attention to how, how often, and how much they feed their babies as they get older. This includes the form, frequency, and amount of food. The mother of the baby can also regularly weigh her child at the posyandu